Preliminary results of a simplified aortic valve‐sparing technique: A feasibility study. Issue 9 (21st June 2022) - Modine, Thomas; Piperata, Antonio; Coisne, Augustin; Doisy, Vincent; Mougnier, Agnes; Vincentelli, Andre; Koussa, Mohamed; Pontana, François; Bical, Antoine; Dubrulle, Henri; Montaigne, David
Abstract: Background and Aim of the Study: To evaluate whether the simplified valve‐sparing technique (SVST) implies clinical outcomes comparable or not with those of established David technique in the surgery of aortic root. Methods: We collected the records of patients who had undergone aortic root surgery with the SVST or standard David technique (SDT) at our institution between January 2009 and December 2018. The primary endpoints were the incidence of all‐cause death, reoperation for any reason, and postoperative complications. The secondary endpoint was the midterm incidence of reoperation for aortic valve regurgitation. Results: A total of 169 patients who underwent aortic root surgery were analyzed. SDT and SVST were performed in 48 (28.4%) and in 121 (71.6%) patients, respectively. Thirty‐day mortality occurred in 0% and 0.8% of patients in the SDT and SVST groups, respectively. The rate of postoperative new permanent pacemaker implantation was 6.3% (three patients) and 0.8% (one patient) in SDT and SVST cohort, respectively ( p = .07). The incidence of postoperative thromboembolic stroke was 6.3% and 2.5% in SDT and SVST groups, respectively ( p = .23). The median follow‐up time was 29 (23–47) months. During the FU period, no differences were found between two cohorts in terms of all‐cause mortality ( p = .99), the incidence of reoperation ( p = .19), and incidence of aortic valve regurgitation requiring reoperation ( p = .58). Conclusions: The SVST appears to be safe and feasible showing early clinical results comparable to the SDT. Nevertheless, further studies with larger series and long‐term follow‐ups are required to demonstrate its safety and efficacy.